Electrical engineers' handbook : (John Wiley and Sons inc, 1967)
This plan met with such enthusiastic response that it has been continued in the fourth edition. The growth of knowledge and the greater degree of specialization in the various phases of electrical engineering have necessitated a considerable enlargement of both volumes.